Brand Image, Environmental Concern, Emotional Desire, and Product Quality in Purchase Decisions - Tri Esti Masita; P. Edi Sumantri; Randita Kusuma P. Cahyani; Apriliani (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Purchase decisions constitute a central concern in marketing research; however, empirical evidence regarding the combined effects of brand image, environmental concern, emotional desire, and perceived product quality on consumers’ purchase decisions for EIGER products in Purwokerto remains limited. This study aims to examine the influence of these four factors on consumers’ purchase decisions. A quantitative survey design was employed, involving 100 EIGER consumers in Purwokerto selected through incidental sampling. Data were collected using structured questionnaires and analyzed through multiple linear regression. The findings demonstrate that brand image, environmental concern, emotional desire, and perceived product quality each have a positive and statistically significant effect on purchase decisions. These results indicate that consumers’ decisions to purchase EIGER products are shaped by the interaction of brand-related perceptions, environmental awareness, emotional motivations, and evaluations of product quality. The study concludes that strengthening these dimensions can enhance consumers’ propensity to purchase EIGER products. These findings contribute to consumer behavior and marketing research by providing empirical evidence on the multidimensional determinants of purchase decisions and offer practical implications for EIGER to strengthen its brand image, maintain consistent product quality, communicate environmental initiatives effectively, and develop stronger emotional connections with consumers.